(untitled) (JURNAL ADMINISTRASI PUBLIK, 2021)
Self-Help Housing Stimulant Assistance (BSPS) or better known as Home Repair is one of the government programs to help people have a decent house as well as a means for social welfare development. This home renovation program has been implemented in many regions in Indonesia. The aim of the researcher in conducting this research was to find out how the Home Improvement Program was implemented in Ranoketang Atas Village. In this study, the researcher focused on the problems found in the field, namely how the implementation of the Home Improvement Program in Ranoketang Atas Village was in accordance with the factors that supported the implementation. According to Ksumanegara (2010), there are four factors that play an important role in the successful implementation of a policy. These factors are communication, resources, disposition, and bureaucratic structure. This study uses a qualitative method. Data is grouped to make it easier to filter which data is needed or not. After grouping the data, the researcher describes it in text form, so that it is better understood, after that the writer draws conclusions from the data so that it can answer the main problem of the research. The result of this research is that the factors that play an important role in the successful achievement of a policy have been fulfilled. Thus, the implementation of the house renovation program in Ranoketang Atas village has gone well. This research is expected to provide benefits for the development of Social Sciences and can be used as a reference for the Ranoketang Atas village government to maintain its performance in the house renov. Keywords: Implementation, Program, Home Improvement, Communication, ation program and improve what is needed for the continuity of the program Resources, Disposition, Bureaucratic Structure.